A new glucosidic phthalide from Helichrysum microphyllum subsp. tyrrhenicum from La Maddalena Island (Sardinia, Italy). Issue 7 (2nd April 2016) - Venditti, Alessandro; Lattanzi, Claudia; Ornano, Luigi; Maggi, Filippo; Sanna, Cinzia; Ballero, Mauro; Alvino, Antonello; Serafini, Mauro; Bianco, Armandodoriano
Abstract : In this study, we reported the analysis of the medium polarity fraction obtained from an accession of Helichrysum microphyllum subsp. tyrrhenicum from La Maddalena Island. Besides several compounds already evidenced in this species and related genera, i.e. micropyrone (1 ), arzanol (2 ), helipyrone (3 ), acetyl-bitalin derivatives (4, 5 ), gnaphaliol (6 ), caffeic acid (7 ), ursolic acid (8 ), 7- O -β-(d -glucopyranosyl)-5-methoxy-1( 3H )-isobenzofuranone (9 ), gnaphaliol-9- O -β-d -glucopyranoside (11 ) and gnaphaliol-3- O -β-d -glucopyranoside (12 ), the presence of a new glycosidic phthalide, 6- O -β-(d -glucopyranosyl)-4-methoxy-1( 3H )-benzofuranone (10 ), was evidenced for the first time, which resulted in a structural isomer of compound (9 ). The occurrence of this new benzofuranone derivative is an additional evidence of the deep intraspecific variability expressed by this species, which was also stated for the non-volatile components, and may be a distinctive trait of the population growing on La Maddalena Island. Abstract :